The secret of the three fates [large type] - Armstrong, Jess (Armstrong, Jess. Ruby Vaughn mystery, 2025)
"The Great War left grieving families willing to sacrifice anything for the chance to say goodbye to a lost loved one. Mr. Owen is no exception. He is desperate to speak to his son, but he doesn't want to face the spirits alone. When the séance--hosted by a trio of mediums billing themselves as The Three Fates--goes awry, Mr. Owen's secrets begin to unravel, threatening to reveal a history that he has been running from for half his life. Something Ruby knows all too well how to do. When Ruby finds one of the Three Fates murdered the night of the séance, she and Mr. Owen quickly become the prime suspects. To clear their names, Ruby enlists the help of Ruan Kivell, the folk healer Pellar who helped her weeks before in Cornwall. As their investigation progresses, Ruby and Ruan realize someone is determined to prevent them from uncovering the truth about what happened to the dead medium."--